Blood-stage challenge for malaria vaccine efficacy trials: a pilot study with discussion of safety and potential value. - Sanderson, F; Andrews, L; Douglas, A; Hunt-Cooke, A; Bejon, P; Hill, A (2008)
There is increasing interest in malaria vaccines targeting the asexual blood stage of Plasmodium falciparum. Without accepted immunologic correlates of clinical protection, challenge studies are useful for assessing the efficacy of candidate vaccines in vivo in healthy volunteers. We report a pilot study of a safe and robust challenge protocol using a blood-stage inoculum. We have applied well-validated trial endpoints and twice daily real-time quantitative polymerase chain reaction monitoring of parasitemia to blood-stage challenge, which enabled direct comparison with sporozoite challenge. We found that greater accuracy in quantification of blood-stage growth rates can be achieved with blood-stage challenge. This finding may provide greater power to detect partial efficacy of many blood-stage candidate vaccines. We discuss the potential utility of blood-stage challenge studies in accelerating malaria vaccine development.